Students' Perceptions of the Implementation of Audio-Visual Media in Learning Islamic Jurisprudence Prayer at MI Al-Alif Darussalam Cikarang - Ginianisa Tri Sekar Wulan; Danang Dwi Basuki (Prodi PGMI STIT Sunan Giri Bima, 2025)
This study aims to describe students' perceptions of the implementation of audio-visual media in learning Islamic jurisprudence (fiqh) prayer at MI Al-Alif Darussalam Cikarang. The background of this study is the importance of an innovative approach in Islamic jurisprudence learning, which tends to be abstract and normative, so that audio-visual media is used to improve student understanding and engagement. This study used a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation. The results showed that most students responded positively to the use of audio-visual media. They felt the material became easier to understand, more interesting, and more memorable. However, several obstacles were also found, such as limited facilities, technical constraints, and the need to improve teacher competency in managing media. In conclusion, audio-visual media is effective in improving the quality of Islamic jurisprudence learning if supported by adequate infrastructure and appropriate learning strategies.